Solid electrolyte and precursor thereof
By using specific ionic liquids in solid electrolyte precursors and in-situ polymerization reactions, the problem of flammability and explosiveness of electrolytes in existing lithium-ion batteries is solved, and good matching with high nickel positive electrode materials and high electrochemical stability and safety of the battery are achieved.
Patent Information
- Application Number
- CN202411711702.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
AI Technical Summary
Among existing lithium-ion batteries, commercial organic carbonate electrolytes have safety risks of flammability and explosion, and it is difficult to match high-nickel positive electrode materials, resulting in serious safety risks under high power density.
A precursor of a solid electrolyte, including polymeric monomers, lithium salts, specific ionic liquids and solvents, is used to generate electrolyte materials adsorbed in the support body through in-situ polymerization, thereby improving the compatibility and electrochemical stability of the solid electrolyte with the positive and negative electrodes.
The solid electrolyte is well matched with high nickel positive electrode materials, which significantly improves the electrochemical stability and safety of the battery, and still has relatively stable cycling performance under high pressure.
Smart Images

Figure CN119627204A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a solid electrolyte and a precursor thereof. Background Art
[0002] Lithium-ion batteries are mainly used in mobile phones, laptops, electric bicycles, portable power banks and other fields due to their high energy density, low self-discharge, no memory effect, fast charge and discharge, and environmental protection. As society attaches great importance to environmental issues, finding lithium batteries with high specific energy can meet the current greater power demand. Currently, the energy used for power vehicles is mainly lithium iron phosphate batteries, but the specific capacity of lithium iron phosphate is low, and it will cause the positive electrode material to break under high voltage conditions.
[0003] High-nickel ternary materials have high specific capacity and long cycle life. The three elements have a good synergistic effect and have good high-voltage resistance. The electrolyte is equivalent to the "blood" of the battery and plays a vital role in the entire battery system. Commercial organic carbonate electrolytes are flammable and explosive, and there are serious safety hazards at high power density. They cannot match high-nickel positive electrode materials well. Therefore, it is of great significance to study and prepare a high-voltage resistant electrolyte, especially to match high-nickel positive electrode materials so that they can give full play to their high power density. Summary of the invention
[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a solid electrolyte precursor, which uses ionic liquid as an additive and has the advantages of low vapor pressure, wide temperature adaptability, wide electrochemical window, good chemical and electrochemical stability, and green environmental protection.
[0005] A second object of the present invention is to provide a solid electrolyte.
[0006] A third object of the present invention is to provide a solid-state battery.
[0007] A fourth object of the present invention is to provide a method for preparing the above-mentioned solid-state battery.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a precursor of a solid electrolyte, comprising the following preparation raw materials: a polymer monomer, a lithium salt, an ionic liquid, and a solvent; the ionic liquid comprises a cation and an anion, and the cation of the ionic liquid comprises at least one of a fluoroalkylphenylpyrrolium ion, a fluoroalkylphenylimidazolium ion, or a fluoroalkylphenylpiperidinium ion.
[0010] The solid electrolyte precursor according to the first aspect of the present invention has at least the following beneficial effects:
[0011] The present invention introduces a fluoroalkylphenyl functional group on the basis of pyrrole, imidazolium or piperidinium ions, and the obtained ionic liquid is conducive to forming a dense and uniform composite organic-inorganic SEI film on the negative electrode metal surface, thereby improving the compatibility of the solid electrolyte with the negative electrode; and the ionic liquid can expand the electrochemical window of the solid electrolyte and improve the lithium ion conductivity. In addition, the solid electrolyte prepared by the precursor of the present invention has good wettability and compatibility with the positive electrode material of the battery, which is beneficial to forming a dense and uniform CEI film and significantly improving the electrochemical stability of the battery.
[0012] In some specific embodiments of the present invention, the cation of the ionic liquid includes at least one of trifluoromethylphenylpyrrolium ion, trifluoromethylphenylimidazolium ion or trifluoromethylphenylpiperidinium ion.
[0013] In some specific embodiments of the present invention, the anion of the ionic liquid includes at least one of a halogen ion, a tetrafluoroborate ion, a hexafluorophosphate ion or a bis(trifluoromethylsulfonyl)imide anion.
[0014] In some specific embodiments of the present invention, the mass concentration of the ionic liquid in the raw material for preparing the electrolyte precursor is 0.01-15%.
[0015] In some specific embodiments of the present invention, the polymerizable monomer is selected from alkylene oxide monomers.
[0016] In some specific embodiments of the present invention, the alkylene oxide monomer includes 1,3-dioxolane, 1,3-dioxane or a combination thereof.
[0017] In some specific embodiments of the present invention, the solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate or trifluoropropylene carbonate.
[0018] In some specific embodiments of the present invention, the volume ratio of the polymerizable monomer to the solvent is 1:(0.1-2).
[0019] In some specific embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium nitrate, lithium perchlorate or lithium tetrafluoroborate.
[0020] In some specific embodiments of the present invention, the molar concentration of the lithium salt in the raw material for preparing the electrolyte precursor is 0.1 to 5 mol / L.
[0021] The second aspect of the present invention provides a solid electrolyte, comprising a support and an electrolyte material adsorbed in the support; the raw materials for preparing the electrolyte material include the precursor described in the first aspect of the present invention; the electrolyte material contains a polymer, and the polymer is prepared by an in-situ polymerization reaction between a polymerization monomer and a lithium salt.
[0022] The solid electrolyte according to the second aspect of the present invention has at least the following beneficial effects:
[0023] By using the precursor of the first aspect of the present invention, the polymerization monomer and the lithium salt are subjected to an in-situ polymerization reaction to generate an electrolyte material adsorbed in the support body. The obtained solid electrolyte has good contact performance with the positive and negative electrode interfaces, and is beneficial to enhancing the transmission of lithium ions in the solid electrolyte and improving the electrochemical performance.
[0024] In some specific embodiments of the present invention, the support body includes at least one of a glass fiber separator, a polyethylene separator, a polypropylene separator or a cellulose acetate separator.
[0025] The third aspect of the present invention provides a solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte arranged between the positive electrode and the negative electrode; the solid electrolyte is the solid electrolyte described in the second aspect of the present invention.
[0026] The solid-state battery according to the third aspect of the present invention has at least the following beneficial effects:
[0027] The solid electrolyte of the second aspect of the present invention has the advantages of high lithium ion conductivity, high energy density, good electrochemical stability and high safety, and still has relatively stable cycle performance under high voltage, and can produce a solid-state battery with excellent electrochemical performance.
[0028] In some specific embodiments of the present invention, the negative electrode is selected from lithium.
[0029] The solid electrolyte of the second aspect of the present invention is particularly suitable for cooperation with a lithium negative electrode, and the obtained lithium ion battery has good electrochemical performance.
[0030] In some specific embodiments of the present invention, the positive electrode includes lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LCO) or a combination thereof.
[0031] The solid electrolyte of the second aspect of the present invention is particularly suitable for cooperation with a lithium nickel cobalt manganese oxide positive electrode and / or a lithium cobalt oxide positive electrode, and the resulting solid-state battery exhibits good electrochemical properties at room temperature, especially a high capacity retention rate.
[0032] The fourth aspect of the present invention provides a method for preparing the solid-state battery described in the third aspect of the present invention, comprising the following steps: applying the raw materials for preparing the electrolyte material to a support, then assembling into a battery, and performing an in-situ polymerization reaction to obtain the solid-state battery.
[0033] The method for preparing a solid-state battery according to the fourth aspect of the present invention has at least the following beneficial effects:
[0034] In the raw materials for preparing electrolyte materials, the polymerizable monomers and lithium salts can undergo an in-situ polymerization reaction (such as ring-opening polymerization), thereby generating electrolyte materials adsorbed in the support body. Based on this process, solid-state batteries are assembled. The preparation process is simple and easy to operate, the reaction conditions are mild, and there is no pollution to the environment, which is suitable for mass production.
[0035] In some specific embodiments of the present invention, the in-situ polymerization reaction time is 24 to 72 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a synthetic route diagram of the ionic liquids of ionic liquid preparation examples 1 to 2.
[0037] Figure 2 This is a reaction mechanism diagram of the in-situ polymerization reaction of the polymerizable monomer and the lithium salt in Application Example 1.
[0038] Figure 3 The electrochemical window performance curves of the solid electrolytes prepared from the samples of Example 1 and Comparative Examples 1-2 at room temperature.
[0039] Figure 4 The room temperature interface impedance curves of the lithium ion batteries of Application Example 1 and Comparative Examples 1-2 are shown.
[0040] Figure 5 The cycle curves of the lithium ion batteries of Application Example 1 and Comparative Examples 1-2 are cycled 150 times at 1C.
[0041] Figure 6 The figure is a cycle curve of the lithium ion battery of Application Example 5 cycled 400 times at 1C. DETAILED DESCRIPTION
[0042] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following preparation examples, embodiments and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0043] A first aspect of an embodiment of the present invention provides a precursor for a solid electrolyte, comprising the following preparation raw materials: a polymer monomer, a lithium salt, an ionic liquid, and a solvent; the ionic liquid comprises a cation and an anion, and the cation of the ionic liquid comprises at least one of a fluoroalkylphenylpyrrolium ion, a fluoroalkylphenylimidazolium ion, or a fluoroalkylphenylpiperidinium ion.
[0044] The present invention introduces a fluoroalkylphenyl functional group on the basis of pyrrole, imidazolium or piperidinium ions, and the obtained ionic liquid is conducive to forming a dense and uniform composite organic-inorganic SEI film on the negative electrode metal surface, thereby improving the compatibility of the solid electrolyte with the negative electrode; and the ionic liquid can expand the electrochemical window of the solid electrolyte and improve the lithium ion conductivity. In addition, the solid electrolyte prepared by the precursor of the present invention has good wettability and compatibility with the positive electrode material of the battery, which is beneficial to forming a dense and uniform CEI film and significantly improving the electrochemical stability of the battery.
[0045] In some embodiments of the present invention, the cation of the ionic liquid includes at least one of trifluoromethylphenylpyrrolium ion, trifluoromethylphenylimidazolium ion or trifluoromethylphenylpiperidinium ion; in some specific embodiments of the present invention, the cation of the ionic liquid includes at least one of 1-(4-(trifluoromethyl)phenyl)pyrrolium ion, 1-(4-(trifluoromethyl)phenyl)imidazolium ion or 1-(4-(trifluoromethyl)phenyl)piperidinium ion; in some examples of the present invention, the cation of the ionic liquid includes 1-(4-(trifluoromethyl)phenyl)pyrrolium ion, 1-(4-(trifluoromethyl)phenyl)imidazolium ion or a combination thereof.
[0046] In some embodiments of the present invention, the anion of the ionic liquid includes at least one of a halogen ion, a tetrafluoroborate ion, a hexafluorophosphate ion or a bistrifluoromethylsulfonyl imide anion; in some specific embodiments of the present invention, the anion of the ionic liquid includes a hexafluorophosphate ion, a bistrifluoromethylsulfonyl imide anion or a combination thereof; in some examples of the present invention, the anion of the ionic liquid is selected from a bistrifluoromethylsulfonyl imide anion.
[0047] In some embodiments of the present invention, the mass concentration of the ionic liquid in the raw material for preparing the electrolyte precursor is 0.01-15%; in some specific embodiments of the present invention, the mass concentration of the ionic liquid in the raw material for preparing the electrolyte precursor is 0.1-12%; in some examples of the present invention, the mass concentration of the ionic liquid in the raw material for preparing the electrolyte precursor is 1-8%. Non-limiting specific examples are 2%, 3%, 4%, 5%, 6% or 7%.
[0048] In some embodiments of the present invention, the polymerized monomer is selected from alkylene oxide monomers; in some specific embodiments of the present invention, the alkylene oxide monomer includes 1,3-dioxolane, 1,3-dioxane or a combination thereof; in some examples of the present invention, the alkylene oxide monomer is selected from 1,3-dioxolane.
[0049] In some embodiments of the present invention, the solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate or trifluoropropylene carbonate; in some specific embodiments of the present invention, the solvent includes at least one of dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate or trifluoropropylene carbonate; in some examples of the present invention, the solvent includes diethyl carbonate, fluoroethylene carbonate or a combination thereof; in some specific examples of the present invention, the solvent is selected from a mixture of diethyl carbonate and fluoroethylene carbonate.
[0050] The use of the above solvent in the present invention is beneficial to improving the compatibility of the solid electrolyte with the positive electrode material, especially with the high-nickel positive electrode material.
[0051] In some embodiments of the present invention, the volume ratio of diethyl carbonate to fluoroethylene carbonate in the solvent is 1: (1-6); in some specific embodiments of the present invention, the volume ratio of diethyl carbonate to fluoroethylene carbonate in the solvent is 1: (1.5-5); in some examples of the present invention, the volume ratio of diethyl carbonate to fluoroethylene carbonate in the solvent is 1: (2-4). Non-limiting specific examples are 1:2.2, 1:2.5, 1:3, 1:3.2 or 1:3.5.
[0052] In some embodiments of the present invention, the volume ratio of the polymerized monomer to the solvent is 1:(0.1-2); in some specific embodiments of the present invention, the volume ratio of the polymerized monomer to the solvent is 1:(0.3-1.5); in some examples of the present invention, the volume ratio of the polymerized monomer to the solvent is 1:(0.5-1). Non-limiting specific examples are 1:0.6, 1:0.7, 1:0.8 or 1:0.9.
[0053] In some embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalate borate, lithium nitrate, lithium perchlorate or lithium tetrafluoroborate; in some specific embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) or lithium difluorooxalate borate; in some examples of the present invention, the lithium salt includes lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalate borate or a combination thereof; in some specific examples of the present invention, the lithium salt is selected from a mixture of lithium bis(trifluoromethanesulfonyl imide and lithium difluorooxalate borate.
[0054] In some embodiments of the present invention, the molar ratio of lithium bis(trifluoromethanesulfonyl imide) to lithium difluorooxalate borate in the lithium salt is 1:(0.5-2); in some specific embodiments of the present invention, the molar ratio of lithium bis(trifluoromethanesulfonyl imide) to lithium difluorooxalate borate in the lithium salt is 1:(0.7-1.5); in some examples of the present invention, the molar ratio of lithium bis(trifluoromethanesulfonyl imide) to lithium difluorooxalate borate in the lithium salt is 1:(0.8-1.2). Non-limiting specific examples are 1:0.9, 1:1 or 1:1.1.
[0055] In some embodiments of the present invention, the molar concentration of lithium salt in the raw material for preparing the electrolyte precursor is 0.1-5 mol / L; in some specific embodiments of the present invention, the molar concentration of lithium salt in the raw material for preparing the electrolyte precursor is 0.5-4 mol / L; in some examples of the present invention, the molar concentration of lithium salt in the raw material for preparing the electrolyte precursor is 1-3 mol / L. Non-limiting specific examples are 1.2 mol / L, 1.5 mol / L, 2 mol / L, 2.2 mol / L or 2.5 mol / L.
[0056] The second aspect of the embodiment of the present invention provides a solid electrolyte, including a support and an electrolyte material adsorbed in the support; the raw materials for preparing the electrolyte material include the precursor of the first aspect of the embodiment of the present invention; the electrolyte material contains a polymer, and the polymer is prepared by an in-situ polymerization reaction of a polymerization monomer and a lithium salt.
[0057] By using the precursor of the first aspect of the embodiment of the present invention, the polymerization monomer and the lithium salt are subjected to an in-situ polymerization reaction to generate an electrolyte material adsorbed in the support body. The obtained solid electrolyte has good contact performance with the positive and negative electrode interfaces, and is beneficial to enhancing the transmission of lithium ions in the solid electrolyte and improving the electrochemical performance.
[0058] In some embodiments of the present invention, the support body includes at least one of a glass fiber separator, a polyethylene separator, a polypropylene separator, or a cellulose acetate separator.
[0059] A third aspect of an embodiment of the present invention provides a solid-state battery, comprising a positive electrode, a negative electrode and a solid-state electrolyte disposed between the positive electrode and the negative electrode; the solid-state electrolyte is the solid-state electrolyte of the second aspect of an embodiment of the present invention.
[0060] The solid electrolyte of the second aspect of the embodiment of the present invention has the advantages of high lithium ion conductivity, high energy density, good electrochemical stability and high safety. It still has relatively stable cycle performance under high voltage and can produce a solid-state battery with excellent electrochemical performance.
[0061] In some embodiments of the present invention, the negative electrode is selected from lithium.
[0062] The solid electrolyte of the second aspect of the embodiment of the present invention is particularly suitable for cooperation with a lithium negative electrode, and the obtained lithium ion battery has good electrochemical performance; the specific lithium ion conductivity can reach 0.41 to 0.83 mS·cm -1 .
[0063] In some embodiments of the present invention, the positive electrode includes lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LCO) or a combination thereof; in some specific embodiments of the present invention, the positive electrode is selected from lithium nickel cobalt manganese oxide (NCM) or lithium cobalt oxide (LCO).
[0064] In some embodiments of the present invention, the nickel cobalt manganese oxide (NCM) includes at least one of NCM111, NCM523, NCM622 or NCM811; in some specific embodiments of the present invention, the nickel cobalt manganese oxide (NCM) is selected from NCM811.
[0065] The solid electrolyte of the second aspect of the embodiment of the present invention is particularly suitable for cooperation with a nickel cobalt manganese oxide lithium positive electrode and / or a lithium cobalt oxide positive electrode. The resulting solid-state battery exhibits good electrochemical properties at room temperature, and specifically can achieve the following performance: at 1C, the capacity retention rate of the solid electrolyte matched with the NCM811 positive electrode after 150 cycles is ≥80.0%; the capacity retention rate of the solid electrolyte matched with the LCO positive electrode after 400 cycles is ≥80.0%.
[0066] The fourth aspect of an embodiment of the present invention provides a method for preparing a solid-state battery according to the third aspect of an embodiment of the present invention, comprising the following steps: applying raw materials for preparing electrolyte materials to a support, then assembling into a battery, and performing an in-situ polymerization reaction to obtain a solid-state battery.
[0067] In the raw materials for preparing electrolyte materials, the polymerizable monomers and lithium salts can undergo an in-situ polymerization reaction (such as ring-opening polymerization), thereby generating electrolyte materials adsorbed in the support body. Based on this process, solid-state batteries are assembled. The preparation process is simple and easy to operate, the reaction conditions are mild, and there is no pollution to the environment, which is suitable for mass production.
[0068] In some embodiments of the present invention, the in-situ polymerization reaction time is 24 to 72 hours; in some specific embodiments of the present invention, the in-situ polymerization reaction time is 30 to 66 hours; in some examples of the present invention, the in-situ polymerization reaction time is 36 to 60 hours. Non-limiting specific examples include 40 hours, 45 hours, 50 hours or 55 hours.
[0069] In some embodiments of the present invention, the temperature of the in-situ polymerization reaction is room temperature, specifically 25°C.
[0070] The present invention is further described below in conjunction with specific examples.
[0071] In the following specific examples, room temperature refers to 20-30° C.; the temperature of the in-situ polymerization reaction is room temperature.
[0072] In the following specific examples, the water content in the glove box is less than 1 ppm, the oxygen content is less than 1 ppm, and the glove box is filled with argon gas; the water content of the solvent is less than 2 ppm, and the water content of the lithium salt is less than 1 ppm.
[0073] Ionic Liquid Preparation Example 1
[0074] This example provides an ionic liquid PY 114 TFSI, synthesis pathway such as Figure 1 The specific preparation steps of a are as follows:
[0075] 1 mmol of 1-(4-(trifluoromethyl)phenyl)pyrrolidine and ethyl acetate (10 mL) were placed in a flask, 1.1 mmol of N-methylbis(trifluoromethanesulfonyl)imide was slowly added, and the mixture was stirred at room temperature for 6 hours. Then 2 g of activated carbon was added and the mixture was stirred overnight. The activated carbon was removed by filtration, and the volatiles were removed under vacuum to obtain a colorless powder solid.
[0076] Ionic liquid preparation example 2
[0077] This example provides an ionic liquid EMPITFSI, the synthesis route is as follows Figure 1 b, the specific preparation steps are as follows:
[0078] 1 mmol of 1-(4-(trifluoromethyl)phenyl)imidazole and ethyl acetate (10 mL) were placed in a flask, 1.1 mmol of N-methylbis(trifluoromethanesulfonyl)imide was slowly added, and the mixture was stirred at room temperature for 6 hours. Then 2 g of activated carbon was added and the mixture was stirred overnight. The activated carbon was removed by filtration, and the volatiles were removed under vacuum to obtain a colorless powder solid.
[0079] Example 1
[0080] This example provides an electrolyte precursor solution, which specifically includes the following preparation steps:
[0081] 1,3-Dioxolane, diethyl carbonate and fluoroethylene carbonate were mixed in a glove box at a volume ratio of 6:1:3 to obtain a mixed solution; then lithium salts of lithium bistrifluoromethylsulfonyl imide and lithium difluorooxalatoborate were added to the mixed solution (so that the concentration of both in the mixed solution was 1 mol / L), and then 5% of the total mass of the electrolyte was added to the ionic liquid PY 114 TFSI (prepared in Preparation Example 1) is mixed evenly, so that the lithium salt, ionic liquid, polymerized monomer and solvent are fully mixed to prepare an electrolyte precursor solution.
[0082] Example 2
[0083] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid PY 114 The amount of TFSI added is 3% of the total mass of the electrolyte, and the remaining raw materials and preparation method are the same as in Example 1.
[0084] Example 3
[0085] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid PY 114 The amount of TFSI added was 10% of the total mass of the electrolyte, and the remaining raw materials and preparation method were the same as in Example 1.
[0086] Example 4
[0087] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid in this example is EMPITFSI (prepared in Preparation Example 2), and the added amount is 5% of the total mass of the electrolyte. The remaining raw materials and preparation method are the same as in Example 1.
[0088] Example 5
[0089] This example provides an electrolyte precursor solution, which is different from Example 3 in that the amount of ionic liquid EMPITFSI added in this example is 3% of the total mass of the electrolyte, and the remaining raw materials and preparation method are the same as those in Example 3.
[0090] Comparative Example 1
[0091] This example provides an electrolyte precursor solution. The difference from Example 1 is that this example does not contain an ionic liquid, and the remaining raw materials and preparation method are the same as those in Example 1.
[0092] Comparative Example 2
[0093] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid in this example is PY 13 TFSI (1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide) was added in an amount of 5% of the total mass of the electrolyte. The remaining raw materials and preparation method were the same as those in Example 1.
[0094] Comparative Example 3
[0095] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid in this example is PP 13 TFSI (1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide) was added in an amount of 10% of the total mass of the electrolyte; and the volume ratio of 1,3-dioxolane, diethyl carbonate and fluoroethylene carbonate was 5:2:3; the remaining raw materials and preparation method were the same as those in Example 1.
[0096] Comparative Example 4
[0097] This example provides an electrolyte precursor solution. The difference from Example 1 is that the ionic liquid in this example is PP 13 TFSI, added in an amount of 3% of the total mass of the electrolyte; and the volume ratio of 1,3-dioxolane, diethyl carbonate and fluoroethylene carbonate is 7:1:2; the remaining raw materials and preparation method are the same as those in Example 1.
[0098] Application Example 1
[0099] This example provides a lithium ion battery, which is prepared by the following preparation method, specifically comprising the following steps:
[0100] (1) Take the electrolyte precursor solution prepared in Example 1.
[0101] (2) Preparation of positive electrode sheet: First, nickel cobalt manganese oxide (NCM811) powder, conductive carbon black, and binder polyvinylidene fluoride are mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone is added and mixed with a stirrer to form a slurry. The slurry is then coated on aluminum foil and dried in an oven at 80°C for 12 h. The slurry is then compacted with a tablet press and cut into positive electrode sheets with a diameter of 14 mm. The slurry is then placed in a vacuum drying oven at 80°C for 12 h, weighed, and placed in a glove box for later use to obtain a positive electrode sheet.
[0102] (3) Assembling the battery: First, place the positive electrode sheet in the middle of the negative electrode shell, then place the support, and then drip a few drops of the electrolyte precursor solution in step (1) on the support, and then place the lithium sheet, steel sheet, gasket and positive electrode shell. Finally, use a battery sealing machine to press the battery tightly and assemble it into a CR2032 button battery. Place it for 48 hours to polymerize it in situ to obtain the lithium-ion battery in this example. In this example, the electrolyte precursor solution is polymerized and solidified in situ in the support to form a solid electrolyte.
[0103] In this example, step (3) involves in situ polymerization of the polymer monomer and the lithium salt (for example, as described in Figure 2 The reaction mechanism shown in the figure is that 1,3-dioxolane (DOL) undergoes ring-opening polymerization under the action of lithium difluorooxalatoborate (LiDFOB) to generate a solid electrolyte material adsorbed inside the support body, which can greatly improve the poor contact between the solid electrolyte and the positive and negative electrodes, and is beneficial to enhance the transmission of lithium ions in the electrolyte.
[0104] Application Example 2
[0105] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Example 2, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0106] Application Example 3
[0107] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Example 3, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0108] Application Example 4
[0109] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Example 4, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0110] Application Example 5
[0111] This example provides a lithium-ion battery, which is different from Application Example 1 in that in this example, lithium nickel cobalt manganese oxide (NCM811) is replaced by lithium cobalt oxide (LCO), and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0112] Application Comparative Example 1
[0113] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Comparative Example 1, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0114] Application Comparative Example 2
[0115] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Comparative Example 2, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0116] Application Comparative Example 3
[0117] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Comparative Example 3, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0118] Application Comparative Example 4
[0119] This example provides a lithium-ion battery. The difference from Application Example 1 is that this example uses the electrolyte precursor solution prepared in Comparative Example 4, and the remaining raw materials and preparation methods are the same as those in Application Example 1.
[0120] Performance Testing
[0121] 1) Electrochemical window performance test
[0122] The samples of Examples 1 to 5 and Comparative Examples 1 to 4 were used to assemble lithium / steel asymmetric batteries, and the electrochemical window performance curves of the assembled batteries were tested at room temperature. Figure 3 The electrochemical window performance curves of the solid electrolytes prepared from the samples of Example 1 and Comparative Examples 1-2 at room temperature. It can be seen from the figure that the electrochemical window of Example 1 is 4.8V, the electrochemical window of Comparative Example 1 is 4.3V, and the electrochemical window of Comparative Example 2 is 4.6V; the solid electrolyte prepared from the electrolyte precursor solution of Example 1 has a high electrochemical window of up to 4.8V, which can meet the voltage requirement of nickel cobalt manganese oxide lithium positive electrode materials.
[0123] 2) Ionic conductivity test
[0124] Steel / steel solid-state batteries were assembled using solid electrolytes prepared from samples of Examples 1 to 5 and Comparative Examples 1 to 4, and the ionic conductivity of the batteries was tested at room temperature. The specific test results are shown in Table 1 below.
[0125] Table 1 Room temperature ionic conductivity of lithium ion batteries prepared using samples of Examples 1 to 5 and Comparative Examples 1 to 4
[0126]
[0127] As shown in Table 1, the solid electrolytes prepared by using the samples of Examples 1 to 5 of the present invention respectively, the obtained lithium ion batteries all have relatively high room temperature ionic conductivity (0.62 to 0.83 mS·cm -1), which are all higher than the room temperature ionic conductivities of Comparative Examples 1 to 4. Therefore, the solid electrolyte prepared by using the samples in the embodiments of the present invention is conducive to obtaining better battery performance.
[0128] 3) Impedance performance test
[0129] At room temperature, the interfacial impedance performance of the lithium-ion batteries assembled by using the NCM811 / lithium battery method in Application Examples 1 to 5 and Application Comparative Examples 1 to 4 was tested. Figure 4 The room temperature interface impedance curves of the lithium ion batteries using Example 1 and Comparative Examples 1-2 show that the batteries using Comparative Examples 1-2 have a large interface impedance, with interface impedance values of approximately 170Ω and 110Ω, while the interface impedance value of the solid-state battery using Example 1 is significantly reduced, with a value of approximately 90Ω, indicating that compared with Comparative Examples 1-2, the solid electrolyte prepared from the precursor solution of Example 1 is more compatible with the nickel cobalt manganese oxide positive electrode material and has better lithium ion transmission capability.
[0130] 4) Cycle performance test
[0131] At room temperature, the cycle performance of the lithium-ion batteries assembled using the NCM811 / lithium battery method in Application Examples 1 to 5 and Comparative Examples 1 to 4 was tested for 150 cycles at 1C, wherein the first two cycles were activated and the cycle performance was calculated from the third cycle. Figure 5 The cycle curves of the lithium ion batteries of Example 1 and Comparative Examples 1-2 after 150 cycles at 1C are shown in the figure. As can be seen from the figure, the discharge specific capacity of the solid-state battery of Example 1 increases from 165.0 to 132.0 mAh·g -1 The capacity retention rate can reach 80.0%, while the discharge specific capacity of the solid-state batteries in Comparative Examples 1 to 2 after 150 cycles increases from 155.6 to 29.1 mAh·g -1 and 158.2 to 108.2 mAh g -1 , the capacity retention rates are 18.7% and 68.4% respectively, which are far inferior to those in Application Example 1.
[0132] In addition, the cycle performance of the lithium-ion battery assembled by LCO / lithium battery in Application Example 5 was tested for 400 cycles at 1C. Figure 6 The cycle curve of the lithium-ion battery of Example 5 after 400 cycles at 1C is shown in the figure. As can be seen from the figure, the initial discharge specific capacity of the solid-state battery of Example 1 is 114.8 mAh·g -1 , the capacity retention rate can reach 80.0% after 400 cycles, indicating that the solid electrolyte prepared from the precursor solution of Example 1 also has good compatibility with the lithium cobalt oxide (LCO) positive electrode material.
[0133] The solid electrolytes prepared from the samples of Examples 1 to 5 of the present invention not only have high ionic conductivity (up to 0.62 to 0.83 mS·cm at room temperature) but also have a high ionic conductivity (up to 0.62 to 0.83 mS·cm at room temperature). -1 , and the trifluorotoluene functional group can help form a good positive and negative electrode interface, greatly improving the stability of the electrochemical cycle of the solid-state battery; and because the solid electrolytes prepared by the samples of Examples 1 to 5 have excellent ion transmission capabilities, the assembled composite solid-state lithium-ion batteries with lithium nickel cobalt manganese oxide and lithium cobalt oxide as positive electrodes have good stability at high currents and room temperature. The solid electrolytes prepared by the samples of Examples 1 to 5 can not only ensure high energy density and safety, but also effectively improve the ionic conductivity of the solid electrolytes. In addition, the solid electrolytes are in contact with the positive and negative electrodes and form a better interface layer, achieving better cycle stability.
[0134] In summary, the precursor in the present invention uses ionic liquid as an additive, which has the advantages of low vapor pressure, wide temperature adaptability, wide electrochemical window, good chemical and electrochemical stability, and green environmental protection. In addition, by using ionic liquids with specific functional groups as additives, a trifluoromethylphenyl functional group is introduced on the basis of pyrrole ions, imidazolium ions or piperidinium ions, and the obtained ionic liquid is conducive to forming a dense and uniform composite organic-inorganic SEI film on the surface of the negative electrode metal, thereby improving the compatibility of the solid electrolyte with the negative electrode; and the ionic liquid can expand the electrochemical window of the solid electrolyte and improve the lithium ion conductivity; in addition, it is also conducive to forming a dense and uniform CEI film, significantly improving the electrochemical stability of the battery. Furthermore, on the basis of using ionic liquid additives with specific functional groups, the ratio of lithium salt concentration, solvent and ionic liquid is adjusted, so that the obtained solid electrolyte is well matched with the positive electrode material, especially with the positive electrode of nickel cobalt manganese oxide and the positive electrode of lithium cobalt oxide. The solid-state lithium ion battery with nickel cobalt manganese oxide as the positive electrode has a capacity retention rate of 80.0% after 150 cycles at a high voltage of 4.3V and 1.0C; the solid-state lithium ion battery with lithium cobalt oxide as the positive electrode has a capacity retention rate of 80.0% after 400 cycles at a high voltage of 4.3V and 1.0C. The solid-state electrolyte provided in the present invention has high lithium ion conductivity and energy density, as well as excellent electrochemical stability and high safety, and can achieve relatively stable cycle performance under high pressure.
Claims
1. A solid electrolyte precursor, characterized in that: The preparation method comprises the following raw materials: a polymer monomer, a lithium salt, an ionic liquid, and a solvent; the ionic liquid comprises a cation and an anion, and the cation of the ionic liquid comprises at least one of a fluoroalkylphenylpyrrolium ion, a fluoroalkylphenylimidazolium ion, or a fluoroalkylphenylpiperidinium ion.
2. The precursor according to claim 1, characterized in that The cation of the ionic liquid includes at least one of trifluoromethylphenylpyrrolium ion, trifluoromethylphenylimidazolium ion or trifluoromethylphenylpiperidinium ion; And / or, the anion of the ionic liquid includes at least one of a halogen ion, a tetrafluoroborate ion, a hexafluorophosphate ion or a bistrifluoromethylsulfonyl imide anion.
3. The precursor according to claim 1, characterized in that The mass concentration of the ionic liquid in the raw material for preparing the electrolyte precursor is 0.01-15%.
4. The precursor according to claim 1, characterized in that The polymerizable monomer is selected from alkylene oxide monomers; preferably, the alkylene oxide monomers include 1,3-dioxolane, 1,3-dioxane or a combination thereof; and / or, the solvent comprises at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate or trifluoropropylene carbonate; And / or, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium nitrate, lithium perchlorate or lithium tetrafluoroborate.
5. The precursor according to claim 1, characterized in that The volume ratio of the polymerizable monomer to the solvent is 1: (0.1~2); And / or, the molar concentration of the lithium salt in the raw material for preparing the electrolyte precursor is 0.1 to 5 mol / L.
6. A solid electrolyte, characterized in that: It comprises a support and an electrolyte material adsorbed in the support; the raw material for preparing the electrolyte material comprises the precursor according to any one of claims 1 to 5; the electrolyte material comprises a polymer, and the polymer is prepared by an in-situ polymerization reaction between a polymerization monomer and a lithium salt.
7. The solid electrolyte according to claim 6, characterized in that The support body includes at least one of a glass fiber separator, a polyethylene separator, a polypropylene separator or a cellulose acetate separator.
8. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode; the solid electrolyte is the solid electrolyte according to claim 6 or 7.
9. The solid-state battery according to claim 8, characterized in that: The negative electrode is selected from lithium; And / or, the positive electrode includes lithium nickel cobalt manganese oxide, lithium cobalt oxide or a combination thereof.
10. A method for preparing a solid-state battery as claimed in claim 8 or 9, characterized in that: The following steps are involved: The raw materials for preparing the electrolyte material are applied to a support body, and then assembled into a battery, and an in-situ polymerization reaction is performed to obtain the solid-state battery.